IoT-Based Socket Control System - Mohd Fadzil, Muhammad Syakir Imam; Mashori, Sumaiya (Progress in Engineering Application and Technology, 2020)
The project aims to develop an IoT-based socket control system for controlling the use of electrical appliances. The socket control system developed able to save on excessive use of electrical appliances and reduce the cost of electricity bills. NodeMCU and smartphones are used to control the overall effectiveness of the project. NodeMCU is connected to Wi-Fi, the socket is controlled using a smartphone connected to the internet. Users can turn the electrical appliance on and off using the Blynk application on a smartphone. Current charge readings and electricity consumption are taken with the addition of current sensors.